Fractographic study of welded joints of carbon fiber/PPS composites tested in lap shear - Miranda Barbosa, Lorena Cristina (2018)
This work shows a fractographic study on fracture surfaces of welded joints by electrical resistance of thermoplastic composites based on polyphenylene sulfide (PPS) reinforced with continuous carbon fiber (CF), evaluated after lap shear loading. The fracture surfaces were generated with the complete breakdown of the specimens under the same conditions used in the mechanical test. The fractographic aspects of fracture surfaces were analyzed by scanning electron microscopy (SEM). SEM analyzes allowed evaluating the interfacial adhesion of fiber/matrix and matrix/heating element (a stainless steel mesh). All laminates showed a well-consolidated composite fracture surfaces, exhibiting cusps, river lines aspects and fibers recovered by a thin layer of polymeric matrix. This latter aspect indicates a strong fiber/matrix interfacial adhesion associated to the presence of voids. Moreover, the matrix/heating element interfacial adhesion was effective only in the laminates with higher lap shear strength values. In these cases, a good adhesion of the matrix was observed in the heating element. The highest strength values determined are attributed to the interdiffusion mechanism of the polymeric chains in the welded region of joints and also to the mechanical anchoring of polymer on the heating element surface. It was also observed the presence of matrix regions with globular aspects indicating unexpected effort in mode I during the lap shear strength test.